Comparative study over methods developed for quantification of darunavir in tablets by environmental friendly infrared and capillary electrophoretic techniques - Kogawa, Ana Carolina [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (My University, 2015)
Darunavir, a protease inhibitor used in the treatment of HIV infection, presents few methods for its determination in pharmaceuticals. Infrared (IR) spectroscopy offers the possibility of obtaining spectra relatively quickly, providing interesting information, analytically, qualitatively or quantitatively. Capillary electrophoresis (CE) performs separations of high efficiency in shorter time with reagents and samples in small quantity. These two methods are cost-benefitted when we evaluate the green level and the cost of analysis. Faster and cheaper methods without generating organic waste by IR and CE for the quantification of darunavir were developed and validated, focusing socioeconomic impact of analytical decisions. If the cost of acquisition, maintenance, production, analysis and conditioning of drugs and pharmaceuticals is high, consequently the price of this product in the market will be higher and it cannot be accessible to the patient. Treatment failure not only affects the quality of life of patients, but also contributes significantly to the economic burden of the health system. In this context there is a tool called Analysis of the Life Cycle, which comes to make us think in a multidimensional way focusing the whole, the parts and especially the interaction among the parts of a system.
Keywords: Capillary electrophoresis; Darunavir; Environmental friendly; Green chemistry; Infrared spectroscopy; Socioeconomic impact